Increasing The Awareness of Students at Montenegrin Universities About the Importance of Sustainable Development - Marija Jankovic (Universitas Diponegoro, 2023)
Today's ecological problems that threaten life on the planet, including global warming, loss of biodiversity, plastic pollution of seas and oceans, are largely unrecognized by individuals and communities. In this sense, scientific institutions should play a key role in developing awareness in the community, especially among students, about the consequences of pollution, the costs of pollution, in such a way as to adopt and promote